SHEAR-WAVE SPLITTING IN A CRITICAL CRUST - III. PRELIMINARY REPORT OF MULTI-VARIABLE MEASUREMENTS IN ACTIVE TECTONICS - Crampin S.; Chastin S.; Gao Y. (My University, 2003)
This is a preliminary report on two sets of recent observations from a region of active tectonics that provide comparatively direct evidence for the critical state of the fluid-saturated microcracked crust. The first data set from crosshole seismics in a controlled source stress-monitoring site (SMS) shows that the crust of the Earth is highly compliant and responds to low-level changes of tectonic stress at substantial distances. The second set of data from earthquake seismograms shows that the seismically active Husavik-Flatey Fault plane is pervaded by critically high pore-fluid pressures, which cause 90° flips in the polarisations of seismic shear waves. We suggest that both sets of observations confirm previous hypotheses for a compliant crack-critical (CCC) crust. This is a new understanding of low-level pre-fracturing deformation that has fundamental implications for a range of applications in solid earth geophysics. These applications range from monitoring hydrocarbon production with time-lapse seismics to monitoring tectonic stress in in situ rock and stress-forecasting the times and magnitudes of impending large earthquakes.
Keywords: 90O FLIPS; COMPLIANT CRACK-CRITICAL (CCC) CRUST; CRACK-INDUCED ANISOTROPY; SHEAR-WAVE SPLITTING; SMS; STRESS-MONITORING SITE